Anomalous charge density wave state evolution and dome-like superconductivity in CuIr2Te4−xSex chalcogenides. (28th September 2021) - Boubeche, Mebrouka; Wang, Ningning; Sun, Jianping; Yang, Pengtao; Zeng, Lingyong; Li, Qizhi; He, Yiyi; Luo, Shaojuan; Cheng, Jinguang; Peng, Yingying; Luo, Huixia
Abstract: We report the anomalous charge density wave (CDW) state evolution and dome-like superconductivity in CuIr2 Te4− x Se x (0 ⩽ x ⩽ 0.5) series. Room temperature powder x-ray diffraction (XRD) results indicate that CuIr2 Te4− x Se x (0 ⩽ x ⩽ 0.5) compounds retain the same structure as the host CuIr2 Te4 and the unit cell constants a and c manifest a linear decline with increasing Se content. Magnetization, resistivity and heat capacity results suggest that superconducting transition temperature ( T c ) exhibits a weak dome-like variation as substituting Te by Se with the maximum T c = 2.83 K for x = 0.1 followed by suppression in T c and simultaneous decrease of the superconducting volume fraction. Unexpectedly, the CDW-like transition ( T CDW ) is suppressed with lower Se doping (0.025 ⩽ x ⩽ 0.2) but re-emerges at higher doping (0.25 ⩽ x ⩽ 0.5). Meanwhile, the temperature-dependent XRD measurements show that the trigonal structure is stable at 20 K, 100 K and 300 K for the host sample and the doping composition with x = 0.5, thus we propose that the behavior CDW-like transition arises from the disorder effect created by chemical doping and is not related to structural transition. The lower and the upper critical fields of these compounds are also addressed.